Differences in Orientation Behavior and Female Attraction by Rhyzopertha dominica (Coleoptera: Bostrichidae) in a Homogeneous Resource Patch. Issue 4 (22nd May 2019) - Cordeiro, Erick M G; Campbell, James F; Phillips, Thomas
Abstract: The objectives of the study are to understand how naïve beetles disperse after emerging as an adult in a homogeneous resource patch. We compared the movement of adult male and female Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) using a laboratory and a field-collected strain during the first 2 d after their emergence from the wheat kernel in which they developed. We first asked if naïve male and female beetles show any innate orientation pattern. Males showed an upward orientation bias during the first day, but not in the second, whereas females had a random pattern of orientation in both days of evaluation. No significant differences were observed between the two strains. Given that males release an aggregation pheromone, we next asked if the upward movement of males improved their ability to be found by a naïve female. The presence of a male, whether above or below a newly emerged female, changed the females' movement direction from random to bias towards the male. In contrast, free-walking males exhibited the same upward movement bias on the first day regardless of the position of the caged male. Only on the second day did male movement change to the opposite direction of the caged male. Here, we report differences between males and females' movement orientation strategies and their response to males producing aggregation pheromone within the grain mass. Our data may improve our understanding of pheromone attraction and help us to develop better monitoring and control tools.